Isoliquiritigenin ameliorates abnormal oligodendrocyte development and behavior disorders induced by white matter injury - Wu, Dong; Zhou, Wenjuan; Du, Jingyi; Zhao, Tiantian; Li, Naigang; Peng, Fan; Li, Anna; Zhang, Xinyue; Zhang, Meihua; Hao, Aijun (Frontiers in Pharmacology, 2024)
Background: White matter injury is a predominant form of brain injury in preterm infants. However, effective drugs for its treatment are currently lacking. Previous studies have shown the neuroprotective effects of Isoliquiritigenin (ISL), but its impact on white matter injury in preterm infants remains poorly understood.Aims: This study aimed to investigate the protective effects of ISL against white matter injury caused by infection in preterm infants using a mouse model of lipopolysaccharide-induced white matter injury, integrating network pharmacology as well as in vivo and in vitro experiments.This study explores the potential mechanisms of ISL on white matter injury by integrating network pharmacology. Core pathways and biological processes affected by ISL were verified through experiments, and motor coordination, anxiety-like, and depression-like behaviors of mice were evaluated using behavioral experiments. White matter injury was observed using hematoxylineosin staining, Luxol Fast Blue staining, and electron microscopy. The development of oligodendrocytes and the activation of microglia in mice were assessed by immunofluorescence.The expression of related proteins was detected by Western blot.We constructed a drug-target network, including 336 targets associated with ISL treatment of white matter injury. The biological process of ISL treatment of white matter injury mainly involves microglial inflammation regulation and myelination. Our findings revealed that ISL reduced early nerve reflex barriers and white matter manifestations in mice, leading to decreased activation of microglia and release of proinflammatory cytokines. Additionally, ISL demonstrated the ability to mitigate impairment in oligodendrocyte development and myelination, ultimately improving behavior disorders in adult mice. Mechanistically, we observed that ISL downregulated HDAC3 expression, promoted histone acetylation, enhanced the expression of H3K27ac, and regulated oligodendrocyte pro-differentiation factors.Conclusions: These findings suggest that ISL can have beneficial effects on white matter injury in preterm infants by alleviating inflammation and promoting oligodendrocyte differentiation.